Design and fabrication of double automatic can crusher / Adib Farhan Badrol Isa and Nurul Hanna Mas’aud - Badrol Isa, Adib Farhan; Mas’aud, Nurul Hanna (School of Mechanical Engineering, 2023)
The world is getting older nowadays and to protect the world, it is required for all human being too aware about the consumption of raw materials, the energy usage in daily life, and aware about the pollution created every day. One of the alternatives to save material is to recycle. There are a lot of things can be recycled, but this project focusing on recycling a tin or aluminium can. In traditional way, a person needs to use their energy to step on the can to make sure the can is compact. This could lead to an injury for that person, and waste time. Therefore, this project is to design and fabricate a double automatic can crusher. The project is conducted by following these methods, design concept, design selection, and fabrication process. The design process is done by using SolidWorks Software. As the design concept has been finalized, the fabrication process will be conducted. In general, this product is controlled using push start and stop button, and the system is using the Human Machine Interface (HMI). Upon completing the fabrication process, the product will be then tested. It is expected that this product able to crush two can at one time, and the can is compact as per required by the recycling centre